Acoplador Triplo Simétrico Planar com Núcleos Intercambiáveis - Martins, Francisco Leonardo Bezerra (2023)
Few studies address linear digital logic all-optical devices, and those that do usually employ microstructured 2D photonic crystals. So far, no research paper proposes such using optical fiber-based devices. This thesis proposes a new three-core optical fiber coupler device, called the interchanging-cores planar three-core fiber coupler (ICPTC coupler). The ICPTC coupler is linear, presents complete switching, and is propagated by low-powered amplitude-modulated pulses. As long as the linearity, dispersion and attenuation conditions are observed, the ICPTC can be made using any optical fiber technology, and operate with pulses of any wavelength. Using our device, we demonstrate the first numerical acquisition of all-optical digital MUX, DEMUX, XOR, XNOR, and half-adder functions using a linear optical fiber-based device. This result is evidence of the possibility of obtaining complex logical processing, even nonlinear logical processing, using only linear fiber design.